AGE SPECIFIC FERTILITY PATTERN LIBYAN WOMEN - تشاریا , فانكا (Dirasat in Economics and Business, 1976)
The study of Libyan fertility is an interesting area of study due to a number of reasons. The prime reason is, that there is almost no fertility control in Libya, thereby yielding estimates of natural fertility of Libyan females. As the oil wealth increased since the revolution in September, 1969, there have been definite improvements in health (including maternal health), nutrition and personal hygiene.